Rancang Bangun Aplikasi Edukasi Sebagai Media Pembelajaran Mengenal Tanaman Untuk Anak Usia Dini Menggunakan Augmented Reality Berbasis Android - Edora Edora (Jurnal SIGMA, 2020)
One of the most common knowledge taught to children is art with a variety of materials such as knowing plants. At present the introduction of plants at an early age still uses picture books and explanations explained by teachers. With Augmented Reality (AR) supported by the markerless method. Users don’t need a special marker in the form of black and white, but use 2D images that are presented in the form of magic cards by the author as a reference to issue 3D objects. In this study several devices with different specifications are used to test whether this application can run well or not. From the results of this study that the marker can be read with a smartphone camera with a response time to detect the marker of approximately 1 second. The minimum distance to detect the marker is 20 cm and the maximum distance is 100 cm. For an optimal distance of 30 cm. The minimum angle for marker detection is 30o and the maximum angle is170o. For an optimal angle of 45o-60o. Keywords : : Learning Media, Augmented Reality, Marker, Markerless, Android, Unity 3D